Diagnostic accuracy of tri-ponderal mass index and body mass index in estimating overweight and obesity in South African children - Violet K. Moselakgomo (African Journal of Primary Health Care & Family Medicine, 2019)
Background: Prevalence of obesity in youths has drastically increased in both industrialised and non-industrialised countries, and this transition resulted in an increased prevalence of chronic diseases.